Pojęcie i klasyfikacja ekspozycji kredytowych stanowiących przedmiot tworzenia rezerw celowych w bankach w Polsce - Orzeszko, Teresa (The Notion of Credit Exposure Classification as the Objective of Specific Provisions Creation in Polish Banks, 2005)
At the forefront of Polish accession to the European Union, another attempt of adjusting regulations regarding the specific provisions to the existing economic reality was taken up, which has been expressed in the Ministry of Finance directive of 10.12.2003, in force commencing January 2004, regarding the principle of provisions creation with reference to the risk connected with banks' activities. Similarly to the preceding regulations, the issued legislative act regulates two basic groups of problems comprising the specific provisions system, i.e. the matter of the subject and the problem of detailed rules regarding their creation. The objective of this article is to clarify and present new regulations referring to issues within the scope of the first of the named above groups. The distinguish - hed seven parts of the article:- point to the evolution of legislation regarding the specific provisions and the reasons of its frequent changes,- define the credit exposure as the objective of specific provisions creation and their current scope,- present possible procedures of credit exposure classification regarding the risk burden and outline the scheme of their classification, following the universal procedure,- characterize detailed principles of credit exposure classification dividing them into:• exposure with reference to State Treasury,• exposure with regard to individual persons, granted for purposes not connected with running business activities or an agricultural farm,• other exposure, present changes introduced in regulations regarding credit exposure, proving more liberal legislation and evaluate their up-to-date version, from the point of view of their transparency.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 182-199